Athletic engagement and athletic identity in top Croatian sprint runners - Babic, V.; Sarac, J.; Missoni, S.; Sindik, J. (Collegium Antropologicum, 2015)
The aim of the research was to determine construct validity and reliability for two questionnaires (Athlete Engagement Questionnaire - AEQ and Athletic Identity Measurement Scale - AIMS), applied on elite Croatian athletes-sprinters, as well as the correlations among the dimensions in these measuring instruments. Then, we have determined the differences in the dimensions of sport engagement and sport identity, according to gender, education level and winning medals on international competitions. A total of 71 elite athletes-sprinters (former and still active) are examined, from which 27 (38%) females and 44 (62%) males. The results of factor analyses revealed the existence of dimensions very similar as in the original instruments, which showed moderate to high reliabilities. A small number of statistically significant correlations have been found between the dimensions of sport engagement and sport identity, mainly in male sprinter runners. Small number of statistically significant differences in the dimensions of sport engagement and sport identity have been found according to the gender, education level and winning medals on the international competitions. The most reasonable explanation of these differences could be given in terms of very similar characteristics of elite athletes on the same level of sport excellence.